2020
DOI: 10.1016/j.bbrep.2020.100818
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of targeted cell death and elimination by near-infrared femtosecond laser ablation

Abstract: The techniques for inducing the death of specific cells in tissue has attracted attention as new methodologies for studying cell function and tissue regeneration. In this study, we show that a sequential process of targeted cell death and removal can be triggered by short-term exposure of near-infrared femtosecond laser pulses. Kinetic analysis of the intracellular accumulation of trypan blue and the assay of caspase activity revealed that femtosecond laser pulses induced immediate disturbance of plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…This is in line with reports showing that caspase-1 activation in Gsdmd -deficient mouse macrophages engages rapid apoptosis via Bid cleavage 1416 . Of note, while mouse caspase-11 is apparently not able to induce this type of apoptosis 79 , we found that optoCaspase-4 and −5 caused GSDMD-independent apoptosis, which could possibly be due to their wider substrate profile 17 . OptoCaspase activation efficiently induced pyroptosis in commonly used laboratory cell lines, such as MCF7 cells, HeLa, Caco-2, HT-29 and HaCaT, ( Fig.…”
Section: Resultsmentioning
confidence: 55%
See 3 more Smart Citations
“…This is in line with reports showing that caspase-1 activation in Gsdmd -deficient mouse macrophages engages rapid apoptosis via Bid cleavage 1416 . Of note, while mouse caspase-11 is apparently not able to induce this type of apoptosis 79 , we found that optoCaspase-4 and −5 caused GSDMD-independent apoptosis, which could possibly be due to their wider substrate profile 17 . OptoCaspase activation efficiently induced pyroptosis in commonly used laboratory cell lines, such as MCF7 cells, HeLa, Caco-2, HT-29 and HaCaT, ( Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Whereas other laser-based methods (such as laser ablation, laser-induced DNA-damage or photosensitizers, such as KillerRed) can also be used to induce cell death rapidly, in selected cells and in vivo [41][42][43][44][45] , they often fail to elicit specific cell death modes, rather relying on less specific types of cellular damage 46 . Laser ablation for example induces mixed apoptotic and necrotic phenotypes 7,8 , which limits its application to study the response of cells or tissue to specific types of PCD. By contrast, the optoCDE approach enables highly specific activation of selected cell death programs directly at effector protein level, increasing the specificity of cell death program and reducing the impact of endogenous regulation and inter-pathway crosstalk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimentally, such analyses are hindered by the low specificity of cell death-inducing stimuli, which affect both the targeted cell and its neighbors, the crosstalk between different PCD pathways, and the difficulty to induce death in a spatially and temporally controlled manner. Laser-induced ablation of single or multiple cells ( Okano et al, 2020 ; Tirlapur et al, 2001 ; Uchugonova et al, 2008 ) has been used to overcome these obstacles, as it allows to study the signaling response of direct neighbors and dead cell extrusion. However, it is unclear what type of death is caused by laser ablation since dying cells often display features of both apoptosis (caspase activation) and necrosis (membrane permeabilization; Tirlapur et al, 2001 ).…”
Section: Introductionmentioning
confidence: 99%